Women and African Labour Force: A Retrospective Analysis - Abiye Gobo, Prisca; Ada Okede, Anthonia (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The International Day of the Girl Child is celebrated annually to empower and amplify the voices of young girls around the world. However, it is still tough being a woman in Africa because culturally, women are seen as inferior. Women face sexism in the work place, public places and even in their homes. They have to deal with gender stereotypes at work and their economic and social rights are violated daily either deliberately or out of ignorance. There is serious gender inequality in employment and the African labour force. This article will interrogate the policies and practices that impede the participation of women in the African labour force. It will examine the harmful practices in employment and how women have risen and can rise above them. Discussing this within the African context, the multidisciplinary approach to historical writing will be utilized to gather the facts and interpret them objectively. The conclusion will emphasize the fact that it is imperative to stop trivializing this issue and give it the seriousness it deserves. After all, directly or indirectly, it affects us all and requires our collective input to tackle it.